A 96-well microplate bioreactor platform supporting individual dual perfusion and high-throughput assessment of simple or biofabricated 3D tissue models. Issue 18 (17th August 2018) - Parrish, J.; Lim, K. S.; Baer, K.; Hooper, G. J.; Woodfield, T. B. F.
Abstract : A microplate-based bioreactor was developed to support dual perfusion of parenchymal and barrier tissues for high-throughput microphysiological system (MPS) studies. Abstract : Traditional 2D monolayer cell cultures and submillimeter 3D tissue construct cultures used widely in tissue engineering are limited in their ability to extrapolate experimental data to predict in vivo responses due to their simplistic organization and lack of stimuli. The rise of biofabrication and bioreactor technologies has sought to address this through the development of techniques to spatially organize components of a tissue construct, and devices to supply these tissue constructs with an increasingly in vivo -like environment. Current bioreactors supporting both parenchymal and barrier tissue constructs in interconnected systems for body-on-a-chip platforms have chosen to emphasize study throughput or system/tissue complexity. Here, we report a platform to address this disparity in throughput and both system complexity (by supporting multiple in situ assessment methods) and tissue complexity (by adopting a construct-agnostic format). We introduce an ANSI/SLAS-compliant microplate and docking station fabricated via stereolithography (SLA), or precision machining, to provide up to 96 samples (Ø6 × 10 mm) with two individually-addressable fluid circuits (192 total), loading access, and inspection window for imaging during perfusion. Biofabricated ovarian cancer models were developed to demonstrate the in situ assessment capabilities via microscopy and a perfused resazurin-based metabolic activity assay. In situ microscopy highlighted flexibility of the sample housing to accommodate a range of sample geometries. Utility for drug screening was demonstrated by exposing the ovarian cancer models to an anticancer drug (doxorubicin) and generating the dose–response curve in situ, while achieving an assay quality similar to static wellplate culture. The potential for quantitative analysis of temporal tissue development and screening studies was confirmed by imaging soft- (gelatin) and hard-tissue (calcium chloride) analogs inside the bioreactor via spectral computed tomography (CT) scanning. As a proof-of-concept for particle tracing studies, flowing microparticles were visualized to inform the design of hydrogel constructs. Finally, the ability for mechanistic yet high-throughput screening was demonstrated in a vascular coculture model adopting endothelial and mesenchymal stem cells (HUVEC-MSC), encapsulated in gelatin-norbornene (gel-NOR) hydrogel cast into SLA-printed well inserts. This study illustrates the potential of a scalable dual perfusion bioreactor platform for parenchymal and barrier tissue constructs to support a broad range of multi-organ-on-a-chip applications.